Participation of a Chosen Company in EU Tenders - Šatková, Jana; Starka, Jan; Vysoká škola ekonomická v Praze. Fakulta managementu (2007)
The thesis is focused on introduction of basic facts about EU tenders (who publish them, where they are published etc.) and elaborating a detailed project according to specifications of a particular EU tender in the field of translation industry to enable chosen company to succeed and pass really strict requirements and procedures EU bodies apply
Vedoucí práce: Jan Starka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze, Fakulta managementu, 2007
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2007
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses